Fully flexible strain sensor from core-spun elastic threads with integrated electrode and sensing cell based on conductive nanocomposite. (3rd May 2018) - Liu, Ping; Pan, Weidong; Liu, Yue; Liu, Jian; Xu, Wenrui; Guo, Xiaohui; Liu, Caixia; Zhang, Yugang; Ge, Yunjian; Huang, Ying
Abstract: A fully flexible strain sensor from core-spun elastic threads with integrated electrode and sensing cell based on conductive nanocomposite is successfully prepared by a simple coating-drying process. It not only avoids mechanical failure at the junction between the sensing cell and electrode during the stretching process but also easily connect with external equipment or circuit. The conductive nanocomposite used for electrode and sensing cell is manufactured by carbon black/sliver paste/poly (sodium-p-styrenesulfonate) and single-walled carbon nanotubes/carbon black, respectively. The integrated strain sensor shows a typical resistive behavior and the gauge factor calculated at 0–50% strain is 2.18, which is close to that of the traditional metallic strain sensor. The integration sensor exhibits fast response (∼125 ms), excellent stability and durability. The integrated strain sensor could be fabricated into various ideal shapes and located in different places. This new strain sensor is applicable to many situations such as monitoring the liquid level in the container, detecting the density of the solution, measuring acceleration and monitoring human movement.